Is hysteroscopy a routine investigation before assisted reproductive techniques? - Maryam Javadian; Seddigheh Esmaeilzadeh; Mehrnaz Farzadmanesh; Masoumeh Golsorkhtabar- Amiri (Babol University of Medical Sciences, 2015)
Introduction: Infertility is a common problem as it is observed in 10 - 15% of couples to whom developing approaches for treatment is an issue of utmost importance. The aim of the current study was to determine the accuracy of diagnostic transvaginal ultrasongraphy (TVS) for the investigation of uterin pathologies in women before the application of assisted reproductive technique (ART). Methods: In this observational, cross-sectional study, TVS and diagnostic hysteroscopy were performed consecutively on 100 infertile women, who were candidates for ART. All the findings of TVS were compared with hysteroscopic appearance of uterine cavity. The sensitivity, specificity, and positive and negative likelihood ratios were also calculated for diagnostic polyp and uterine anomalies. Results: Polyp was detected through diagnosis hysteroscopy in 6 cases (6.0%), out of whom 4 were diagnosed by TVS. The sensitivity and specificity ratios with TVS, diagnosed for polyp, were 50.00% and 98.94%, respectively. In addition, the sensitivity and specificity ratios with TVS, diagnosed for uterine abnormalities were 27.78 % and 98.78%, respectively. Conclusion: The researchers concluded that TVS allows for the diagnosis of polyp uterine in the most cases, but its sensitivity for diagnosis of uterine anomalies is low. Therefore, TVS is not useful technique, compared with hysteroscopy, in patients who are candidates for ART. Thus, hysteroscopy is highly recommended.